Inventory of High-Abundance mRNAs in Skeletal Muscle of Normal Men - Welle, Stephen (Cold Spring Harbor Laboratory Press, 1999)
The serial analysis of gene expression (SAGE) method was used to generate a catalog of 53,875 short (14 base) expressed sequence tags from polyadenylated RNA obtained from vastus lateralis muscle of healthy young men. Over 12,000 unique tags were detected. The frequency of occurrence of each tag reflects the relative abundance of the corresponding mRNA. The mRNA species that were detected 10 or more times, each comprising ≥0.02% of the mRNA population, accounted for 64% of the mRNA mass but <10% of the total number of mRNA species detected. Almost all of the abundant tags matched mRNA or EST sequences cataloged in GenBank. Mitochondrial transcripts accounted for ∼20% of the polyadenylated RNA. Transcripts encoding proteins of the myofibrils were the most abundant nuclear-encoded mRNAs. Transcripts encoding ribosomal proteins, and those encoding proteins involved in energy metabolism, also were very abundant. The database can be used as a reference for investigations of alterations in gene expression associated with conditions that influence muscle function, such as muscular dystrophies, aging, and exercise.